A rare case of esophageal variceal bleeding from portal hypertension due to extrahepatic portal vein obstruction in a two-year-old - Babu, Dhanya; Priya, A.; Yadav, K. Arun Chander (International Journal of Basic & Clinical Pharmacology, 2024)
Extrahepatic portal vein obstruction (EHPVO) is a type of liver vascular disease characterized by cavernomatous transformation and obstruction in the portal veins. Congenital defects, numerous transfusions, trauma, sepsis, dehydration, and hypercoagulable disorders are important risk factors. Since most patients have no symptoms, acute extrahepatic portal vein obstruction is frequently disregarded. Hematemesis and splenomegaly without hepatic decompensation are among the symptoms that might occur in subacute and chronic stages. Imaging studies aid in the diagnosis; Doppler imaging is added to ultrasonography to visualize portal vein blood flow. MRI and CT scans are used to visualize portal vein blockage. Prevention of acute bleeding is the cornerstone in the management. Studies have shown that transhepatic thrombolysis is the preferred choice to avoid systemic side effects. Treatment for extrahepatic portal venous thrombosis involves an intrahepatic portosystemic shunt, which is usually followed by conservative measures to stop variceal haemorrhage. When other forms of therapy are ineffective, liver transplantation is carried out. This case report describes a rare instance of EHPVO in a two-year-old boy who was hospitalized due to recurrent fever, increased belly circumference, and a persistent feeling of fullness in the abdomen. The patient had a surgically placed splenorenal shunt, which helped him respond well to treatment.